A new tribological approach on metal cup with optimized pits model using spark discharge machine. (3rd March 2016) - Razak, D. M.; Syahrullail, S.; Sapawe, N.; Azli, Y.; Nuraliza, N.
ABSTRACT: An interference friction causes tear and wear in metal-on-metal (MoM) hip joint. The purpose of this research is to examine the optimization of pit embedded in the acetabular cup using a spark discharge machine. Tribology tests on cup with 8, 21, and 40 pits embedded produced promising results. A modified pin-on-disk tribometer was used to measure the effects of the coefficient of friction and wear on a 28-mm-diameter acetabular cup. Microscopy image analysis was used to examine particle debris and surface disfigurement. This study revealed that the more pits were produced in the hemispherical or curvature cup, the more lubricant was confined inside the pits, and the easier the contact was for MoM. The results also show that the curvature surface modification with pits can positively influence friction and wear and stability optimization of MoM implants.